Analisis Peran Kader Posyandu dalam Pencegahan Stunting di Kelurahan Margoagung, Kapanewon Seyegan, Kabupaten Sleman - Ria Saputri Rejeki; Gerry Katon Mahendra (Journal of Social and Policy Issues, 2023)
The prevalence of stunting in Margoagung Village reached 10.14%, making it the Village with the highest prevalence rate in Kapanewon Seyegan. As a result, a stunting prevention program is required, and it is inextricably linked to the role of cadres, because cadres can influence the success of the Posyandu program, particularly in monitoring the growth and development of toddlers. Based on this, the purpose of this study is to examine the role of Posyandu cadres in preventing stunting in Margoagung Village. The method used in this study is descriptive qualitative with data collection techniques through interviews, observation and documentation. This study involved 12 respondents, namely representatives of community cadres in the Margoagung Village. The findings of this study show that the Posyandu cadres in Margoagung Village have made a positive contribution to the local community in terms of health because they have carried out their duties well. It has also been demonstrated that the community feels the benefits of regularly visiting the Posyandu, one of which is that the community, particularly mothers of toddlers, can detect early and pay more attention to the health of their respective toddlers. Furthermore, despite not carrying out the program optimally, the cadres have successfully implemented a stunting prevention program through specific and sensitive nutrition interventions. According to the study's findings, several barriers to implementation were discovered, including cadres' lack of knowledge about nutrition and toddler health, so they relied on health workers at the Puskesmas